The causative microorganisms and the underlying urological anomalies in children with urinary tract infection - Bhat, Minakshi (International Journal of Contemporary Pediatrics, 2018)
Background: Urinary tract infection (UTI) is among the most common bacterial infection in children and may be a presentation of variety of underlying urinary tract abnormalities. It is important to diagnose and treat UTI to prevent the long-term complications like renal scarring, hypertension and chronic renal failure. The aim of this study was to find the causative organism and underlying urological anomalies in children with UTI. Methods: A prospective study was carried in children (aged between one month to 12 years) admitted with symptomatic UTI in a tertiary hospital from May 2013 to June 2017.The children were investigated for UTI and the urine culture was positive in 121 patients. The confirmed cases of UTI were subjected to imaging studies as per guidelines. Final study included 116 patients as five patients were excluded due to incomplete investigations. Results: Out of 116 patients, 26 (22.41%) were below 1year ,68 (58.62%) were between 1 to 5 year and 22 (18.96%) were more than 5 years of age. There were 44 (37.93%) males and 72 (62.06%) females. E. coli was the commonest organism causing UTI (78.44%). Urinary tract abnormalities were found in 49 (42.24%) cases. VUR was detected in 23 (46.9%). The other urinary tract abnormalities observed include pelviureteric junction (PUJ) obstruction, posterior urethral valve, urolithiasis, bladder neck obstruction, ureterocele, ectopic kidney, cystic kidney, bladder diverticulum, Extrarenal pelvis, and renal scar respectively. Conclusions: In view of underlying urological anomalies and potential for renal parenchymal damage, UTI should be diagnosed at an earliest and imaging studies should be done in all confirmed cases as per guidelines.